NARCISSISTIC PERSONALITY DISORDER (NPD) DALAM RIWAYAT PROFETIK - Siti Maemunah; Muhammad Asgar Muzakki (IAIN Manado, 2024)
Abstract: This article discusses narcissistic behavior in practicing religion as contained in prophetic history. The theme of narcissism amidst the prominence of social media can be said to be always relevant and evergreen, because narcissistic disorders can penetrate all groups. Including people who are labeled pious and diligent in worship. Interestingly, people with NPD even existed in the time of the Prophet, complete with characteristics and indicators of narcissism from modern psychology. Feeling the most right, the most entitled, arrogant, is indeed part of the “adab” chapter which is the main focus of the Islamic taching. So the Prophet taught us a way - or at least one way - to mentally forge a way to ward off the NPD disorder. Through interdisciplinary analysis that combines psychological and historical approaches, this research examines hadiths related to the NPD theme using a thematic-contextual study model. This research aims to contribute to a deeper understanding of narcissistic behavior in a religious context and offers potential solutions to reduce these tendencies.Key Words : Disorder, narcissism, humilityAbstrak Artikel ini membahas tentang perilaku narsistik dalam beragama yang termuat dalam riwayat kenabian. Tema narsisme di tengah prominennya media sosial boleh dibilang selalu relevan dan evergreen, karena gangguan narsistik bisa mempenetrasi semua kalangan. Termasuk orang yang dilabeli saleh dan rajin beribadah sekalipun. Menariknya, pengidap NPD bahkan sudah ada di zaman Nabi lengkap dengan karakteristik dan indikator narsisme dari psikologi modern. Merasa paling benar, paling berhak, angkuh, memang bagian dari bab adab yang menjadi sorotan utama agama Islam. Maka Nabi pun mengajarkan cara –atau sekurang-kurangnya salah satu cara untuk menempa mental guna menepis gangguan NPD tersebut. Melalui analisis interdisipliner yang menggabungkan pendekatan psikologi dan sejarah, penelitian ini meneliti hadis-hadis berkaitan dengan tema NPD dengan model kajian tematik-kontekstual. Penelitian ini bertujuan untuk berkontribusi pada pemahaman yang lebih mendalam tentang perilaku narsistik dalam konteks agama dan menawarkan solusi potensial untuk mengurangi kecenderungan tersebut.Kata Kunci : Gangguan, narsisme, kerendahan hati.